Role of risk of malignancy index for evaluation and preoperative detection of pelvic malignancies compared with pathological diagnosis - Yousseff, Beenish; Qurieshi, Mariya Amin; Yousseff, Nadiya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Risk of malignancy index (RMI) is widely employed in the developed world in predicting malignant pelvic masses. The present study designed to confirm the effectiveness of the RMI to identify cases with high potential of ovarian malignancy, among patients with an adnexal mass. Methods: This was a cross-sectional study was conducted over a period of two years in a government run tertiary healthcare centre of Srinagar, Kashmir, Jammu and Kashmir, India. Study included 72 patients who underwent surgery due to adnexal mass and were evaluated for ovarian malignancy by comparing RMI with histopathological diagnosis. Data collected included demographic characteristics, ultrasound findings, menopausal status, CA125 levels, and histopathological diagnosis. For each patient, RMI was calculated as per the standard formula. Results: Analysis revealed ultrasound score had the highest sensitivity of 72.7%, while an RMI score ≥250 had the highest specificity of 88.5%. The latter also had the highest positive predictive value of 50%, while negative predictive value was highest for an ultrasound score of 3 (94%). The cut off points based on ROC analysis demonstrates significant predictive ability for ovarian cancer for both RMI and CA125 with AUC to the tune of 82.9% and 80.1% respectively. Conclusions: RMI is a simple score system which can be applied directly into clinical practice and might be of value in pre-operative assessment, and hence selecting patients who need surgical team including gynecologic oncologists.